1993
DOI: 10.1002/art.1790060204
|View full text |Cite
|
Sign up to set email alerts
|

Medical student use of history and physical information in diagnostic reasoning

Abstract: Clinical data gathering is central to clinical competence. Although research has demonstrated the value to experienced clinicians of information obtained from the history, little is known of how medical students use this information. In the present study, two case simulations (in rheumatoid arthritis and systemic lupus erythematosis) were developed to assess medical student information gathering and utilization. The results indicate that most of the students were already considering the correct diagnosis as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
1
12
0
1
Order By: Relevance
“…Research using the PMP method has revealed that students making the correct diagnosis at the end of history taking are from 12 times (95%CI= 3-46) to 33 times (95%CI= 5-218) more likely to reach a correct final diagnosis than those who fail to do so. 3 These results are similar to ours in indicating that a correct diagnosis after history taking contributes to making an accurate final diagnosis. Research has shown that diagnostic accuracy is improved by early and thorough problem representation, which is defined by a degree of abstraction from actual findings.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Research using the PMP method has revealed that students making the correct diagnosis at the end of history taking are from 12 times (95%CI= 3-46) to 33 times (95%CI= 5-218) more likely to reach a correct final diagnosis than those who fail to do so. 3 These results are similar to ours in indicating that a correct diagnosis after history taking contributes to making an accurate final diagnosis. Research has shown that diagnostic accuracy is improved by early and thorough problem representation, which is defined by a degree of abstraction from actual findings.…”
Section: Discussionsupporting
confidence: 90%
“…3 When diagnostic accuracy was compared between a case vignette containing all of the required diagnostic information versus the chief complaint format in which questions were asked to obtain information needed to make the diagnosis, there was a significantly lower accuracy rate with the chief complaint format. 9 In the present study, we used the latter format and students had to obtain data themselves, so the accuracy rate may have been lower.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations